2016
DOI: 10.1007/s10620-016-4228-9
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Adenoma Detection Rate in Gastroenterology Fellowship Training

Abstract: Our data suggest that ADR increases after fellows perform >140 colonoscopies under attending supervision, and thereafter surpasses the ADR of attending-only colonoscopies. Some of the differences may be driven by detection of small adenomas. The findings of this study suggest that a higher threshold for number of colonoscopies performed under attending supervision may be needed to achieve adequate ADR during fellowship prior to independent practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 14 publications
3
26
3
Order By: Relevance
“…As mentioned earlier, ADR is the most robust colonoscopy quality metric for practicing gastroenterologists, but the value of ADR as a competency measurement for the evaluation of gastroenterology fellows during their different stages of training is not well established. Limited literature has been published on this topic, with inconsistent results [ 14 - 21 ]. The aim of this study was to calculate ADR and evaluate its utility as a measure of competency for gastroenterology fellows.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, ADR is the most robust colonoscopy quality metric for practicing gastroenterologists, but the value of ADR as a competency measurement for the evaluation of gastroenterology fellows during their different stages of training is not well established. Limited literature has been published on this topic, with inconsistent results [ 14 - 21 ]. The aim of this study was to calculate ADR and evaluate its utility as a measure of competency for gastroenterology fellows.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective tandem colonoscopy study it was found that fellows with a higher colonoscopy volume had lower adenoma miss rates (AMR), and it was estimated that 450 colonoscopies would be required to achieve an AMR of < 25%[ 17 ]. In a retrospective study in which trainees were followed throughout their fellowship training, it was found that fellows’ ADRs and polyp detection rates (PDR) improved when the fellows had conducted > 140 colonoscopies[ 18 ]. There are several limitations to these studies, including the small number of procedures performed by the fellows, inclusion of non-screening colonoscopies in calculating the ADR, and including fellows from various stages of training during only a limited part of their fellowship.…”
Section: Introductionmentioning
confidence: 99%
“…7 ADR of trainees is generally lower than that of experts 23,24 and has been reported to be 23%-36%. [25][26][27] Although a previous study reported no significant difference in ADR between EAC and CAC, 19 differences between these procedures when performed by trainees remain unclear. In the present study, the cecal intubation rate and time were similar between the two groups.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, even though trainees were experienced in performing colonoscopies, ADR and MAP were relatively higher in both the EAC and CAC groups compared to the results of previous studies. [25][26][27] However, we did not investigate ADR of CC, so it is unclear whether ADR improved compared to CC. Furthermore, because we did not investigate the efficacy of EAC and CAC performed by experts, differences between trainees and experts remain unclear.…”
Section: Discussionmentioning
confidence: 99%